The Role of Pastors in Pastoral Counseling for Cell Group Leaders Experiencing Internal Conflict - Johannes S.P. Rajagukguk; Gede Widiada; Bertina Munthe; Dewi Indrawati Panjaitan (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
Cell group leaders occupy a strategic but underexamined position in congregational life because they translate pastoral vision into relational care, discipleship, prayer, and informal spiritual guidance. This conceptual research article examines the role of pastors in pastoral counseling for cell group leaders who experience internal conflict, understood as intrapersonal, relational, moral, and role-based tension arising from leadership pressure, loyalty dilemmas, unresolved interpersonal strain, and spiritual burden. The article aims to construct a practical-theological framework that enables pastors to respond to such conflict without reducing counseling to advice, discipline, or crisis management. Using an integrative literature review and constructive practical-theological synthesis, the study analyzes scholarship on pastoral care, church conflict, Bowen family systems theory, small-group participation, servant leadership, psychological safety, clergy burnout, and organizational conflict. The synthesis generates three main findings. First, internal conflict among cell group leaders is best understood as a multidimensional phenomenon shaped by role ambiguity, anxious triangulation, and spiritual-moral burden. Second, pastors function most effectively as differentiated counselors, mediators, and boundary keepers who combine empathic listening with ethical clarity. Third, pastoral counseling should be embedded in restorative supervision and congregational learning rather than treated as an isolated emergency intervention. The article concludes that pastors need a theologically grounded, psychologically informed, and organizationally responsible counseling model that restores leaders while strengthening the health of the church system.